AN INVESTIGATION OF ENGLISH TEACHING STRATEGIES IN ENHANCING STUDENTS’ VOCABULARY IMPLEMENTED BY A PRE-SERVICE ENGLISH TEACHER - Fatah Huda (Journal of English and Education, 2016)
The need to teach English language appropriately in particular is a challenge for all the teachers in Indonesia. Today, it has become obligatory for the teachers to rethink and renovate their teaching strategies with the changing times. Since there has been a continuous transformation in the teaching methods and techniques all over the world in every subject, methods and techniques for teaching vocabulary need desirable innovation to fulfill students’ need of vocabulary learning. This research was aimed to investigate the strategies used by a pre-service teacher to improve students’ vocabulary and students’ responses toward the teacher’s strategies. A qualitative approach with case study design with a pre-service English teacher was used and 35 students in one junior high school participated in this study. The data were collected through observations, interview, and questionnaire. The results showed that the teacher used varieties of techniques in numerous methods as his teaching strategies, such as Contextual Teaching and Learning with neighborhood walk, Silent way with pictures and crosswords puzzle, and Total Physical Response with gamification, to enhance students’ vocabulary. The srategies are proven to be appropriate to be implemented in the classroom and leads to the vocabulary collection improvement for most students in the classroom.